Sonochemically synthesized green sorbent for the simultaneous removal of trace metal ions: application and estimation of measurement uncertainty through bottom-up approach. (15th September 2017) - Shah, Faheem; Naeemullah,; Shah, Muhammad Raza; Khan, Rafaqat Ali; Ismail, Bushra; Khan, Asad Muhammad; Khan, Abdur Rahman; Ajaz, Humayun
Abstract : Synergistic combination of ESM–PEI as a green biosorbent in a packed cartridge for the removal of Cd, Pb, Ni, and Cu from environmental samples. Abstract : Polyethyleneimine functionalized eggshell membrane (ESM–PEI) as a green biosorbent has been successfully utilized for the removal of toxic metals. ESM–PEI was sonochemically synthesized by cross-linking amine/amide functional groups of ESM with PEI using glutaraldehyde as a cross-linker. This overall functionalization was carried out in an ultrasonic bath. Surface modification of ESM–PEI was confirmed by Fourier transform infrared spectroscopy and scanning electron microscopy. All analytes were easily extracted by the ESM–PEI packed cartridge followed by spectrometric determination. After successful functionalization, the adsorption capacity of ESM–PEI improved almost 25 times over that of ESM. Different variables affecting the extraction efficacy were investigated. Under optimum conditions, the ESM–PEI packed cartridge showed good stability even after >70 adsorption/desorption cycles run while maintaining over 96% analyte recoveries. Validity of the proposed procedure was checked with certified reference materials as well as by assessing its precision (RSD values < 20%) and trueness (relative error < 11%) under day-to-day conditions. The developed procedure has been further validated by following ISO/IEC 17025 recommendations considering the possible uncertainties through a "bottom-up" approach. The proposed procedure was successfully applied to the environmental water samples for the extraction of Cu, Pb, Cd, and Ni, where ESM–PEI was found to be an environmentally friendly, economic, and more rugged biosorbent.